2002
DOI: 10.1248/jhs.48.134
|View full text |Cite
|
Sign up to set email alerts
|

Production of Interleukin-6 and Its Implication in Rats after Subcutaneous Injection of Carbon Tetrachloride.

Abstract: Previously, we have reported that interleukin-6 (IL-6) administration reduces hepatic injury caused by carbon tetrachloride (CCl 4 ) and induces the production of antioxidant proteins, manganese superoxide dismutase and metallothionein. In the present study, we examined whether IL-6 was induced endogenously by CCl 4 administration in rats, and examined the relationship between the levels of IL-6 production and hepatic injury. Plasma samples were periodically collected after s.c. administration of 5 ml/kg of CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…It has been implicated that cytokines such as TNF-α, IL-1, LI-6 and interleukin-10 contribute to liver damage in rats with a single CCl 4 treatment (Czaja et al, 1989(Czaja et al, , 1995DeCicco et al, 1998;Louis et al, 1998;Neubauer et al, 1998;Simeonova et al, 2001;Hojo et al, 2002;Nakamoto et al, 2003;Campo et al, 2004). Edwards et al (1993) have indicated that Kupffer cells cause liver damage in rats with a single CCl 4 treatment possibly by the release of chemoattractants for neutrophils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been implicated that cytokines such as TNF-α, IL-1, LI-6 and interleukin-10 contribute to liver damage in rats with a single CCl 4 treatment (Czaja et al, 1989(Czaja et al, , 1995DeCicco et al, 1998;Louis et al, 1998;Neubauer et al, 1998;Simeonova et al, 2001;Hojo et al, 2002;Nakamoto et al, 2003;Campo et al, 2004). Edwards et al (1993) have indicated that Kupffer cells cause liver damage in rats with a single CCl 4 treatment possibly by the release of chemoattractants for neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory processes in which Kupffer cells, i.e. the resident macrophages of the liver, cytokines such as tumor necrosis factor-α (TNF-α), interleukin-1 (IL-1), interleukin-6 (IL-6) and interleukin-10, and adhesion molecules such as intercellular adhesion molecule-1 are implicated in the development of CCl 4 -induced acute hepatic injury (Czaja et al, 1989(Czaja et al, , 1995ArmendarizBorunda et al, 1991;Edwards et al, 1993;Tower et al, 1994;DeCicco et al, 1998;Louis et al, 1998;Neubauer et al, 1998;Muriel et al, 2001;Simeonova et al, 2001;Hojo et al, 2002;Nakamoto et al, 2003). It is known that neutrophils, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Opposite to this observation , increased plasma or serum IL-6 level was previously recorded in male rats administered with carbon tetrachloride ( CCl 4 ) either subcutaneously (20) , or orally (21) , or in rats administered orally with the neonicotinoid insecticide acetamiprid (22) .…”
Section: Discussionmentioning
confidence: 88%
“…Hojo et al, (20) showed that subcutaneous CCl4 administration to rats induced IL-6 production and the level of IL-6 produced seemed to be inversely correlated with the hepatic marker enzymes level in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Metallothionein (MT) is a small protein that plays a role in protecting against the toxic effects of heavy metals and xenobiotics as well as in drug resistance and free radical scavenging, [1][2][3][4] and MT knockout mice exhibit hypersensitivity to heavy metals, such as a cadmium 5,6) and mercury. 7) MT is known to be one of the factors involved in resistance to cisplatin, and Sato et al reported that MT knockout mice are more sensitive to cisplatin than normal mice.…”
Section: Introductionmentioning
confidence: 99%